Complete plastid genomes from Ophioglossum californicum, Psilotum nudum, and Equisetum hyemale reveal an ancestral land plant genome structure and resolve the position of Equisetales among monilophytes - Grewe Felix; Guo Wenhu; Gubbels Emily A; Hansen A Katie; Mower Jeffrey P (BMC Evolutionary Biology, 2013)
Abstract Background Plastid genome structure and content is remarkably conserved in land plants. This widespread conservation has facilitated taxon-rich phylogenetic analyses that have resolved organismal relationships among many land plant groups. However, the relationships among major fern lineages, especially the placement of Equisetales, remain enigmatic. Results In order to understand the evolution of plastid genomes and to establish phylogenetic relationships among ferns, we sequenced the plastid genomes from three early diverging species: Equisetum hyemale (Equisetales), Ophioglossum californicum (Ophioglossales), and Psilotum nudum (Psilotales). A comparison of fern plastid genomes showed that some lineages have retained inverted repeat (IR) boundaries originating from the common ancestor of land plants, while other lineages have experienced multiple IR changes including expansions and inversions. Genome content has remained stable throughout ferns, except for a few lineage-specific losses of genes and introns. Notably, the losses of the rps16 gene and the rps12i346 intron are shared among Psilotales, Ophioglossales, and Equisetales, while the gain of a mitochondrial atp1 intron is shared between Marattiales and Polypodiopsida. These genomic structural changes support the placement of Equisetales as sister to Ophioglossales + Psilotales and Marattiales as sister to Polypodiopsida. This result is augmented by some molecular phylogenetic analyses that recover the same relationships, whereas others suggest a relationship between Equisetales and Polypodiopsida. Conclusions Although molecular analyses were inconsistent with respect to the position of Marattiales and Equisetales, several genomic structural changes have for the first time provided a clear placement of these lineages within the ferns. These results further demonstrate the power of using rare genomic structural changes in cases where molecular data fail to provide strong phylogenetic resolution.